THE JADID MOVEMENT IN TURKESTAN: A SOCIO-PHILOSOPHICAL ANALYSIS OF MODERNIZATION IDEAS (Modern American Journal of Social Sciences and Humanities, 2025)
The article provides a socio-philosophical analysis of the Jadid movement as a modernization process in Turkestan in the late 19th and early 20th centuries. The ideas of the Jadids on enlightenment, the formation of national self-awareness, and the renewal of social structures are examined.